When delays become lethal: A case report of a rare and fatal complication in traumatic carotid cavernous fistula - Yuddy Imowanto; Dwiwardoyo Triyuliarto; Putra, Rico Wicaksana; Fatah Abdul Yasir (Published by Universitas Gadjah Mada, 2025)
Carotid cavernous fistula (CCF) is a rare complication that can be easily missed after blunt traumatic brain injury. It is defined as an abnormal arteriovenous shunt between the carotid artery or its branches with the cavernous sinus. Most cases are traumatic in origin and although not typically life-threatening, carry a risk of serious complications. One of the most fatal complications is spontaneous intracerebral haemorrhage (ICH), occurring only 0.9-2.6% of cases. We report a rare case of a 27 yo female, who sustained traumatic brain and craniofacial injuries in a motor vehicle accident 25 d earlier. She presented with gradual loss of consciousness following ophthalmic symptoms that began 5 d prior to admission. Imaging confirmed the presence of ICH as a complication of traumatic CCF. This case highlights the diagnostic challenges of traumatic CCF and its potential complications. Diagnosis is challenging due to its rare occurrence with variable time interval for symptoms to develop (ranging from several hours to years after the initial injury), non-specific symptoms that may mimic other conditions, and delays in seeking care. Delayed diagnosis can be fatal, leading to visual loss, cerebral infarction, and haemorrhagic events. Rapid recognition and prompt management of traumatic CCF are crucial for preventing complications and achieving complete resolution with low rates of morbidity and mortality.